Novel strain-bend sensor using two-mode optical fiber - Almeida, Sergio F. M.; Salvador, J. F.; Carrara, Sidney L. A. [UNESP] (SPIE, the international society for optics and photonics, 1994)
The bending sensitivity of two-mode fiber sensors is discussed. A phenomenological approach based on an apparent core offset is proposed and verified by an experiment where combined bending and extension are present in the fiber.